Strategies and techniques for teaching english to deaf children at Antonio Jose De Sucre Elementary School who attend the regular education system in 2011 - Paredes, Rosaura (UDELAS, 2011)
This thesis has as fundamental goal, it is to achieve some methodological strategies and techniques for teaching to deaf children, and it will identifiy hoy they can learn english through different activiities with visual material, realia, and other resources. On other hand, it provides to the teachers a guide to facilitate english languaje learning in the classroom withdeaf children. In conclusion, this tool